The Effect of Pressure on Pellet Formation of Polycrystaline Superconductors Ybco Versus Ybcago. - Bidarian, Abe (1999)
Keywords: dept.phy; faculty_collection; sabbatical_report

Laboratory Research in Spectral Attenuation in Optical Fibers. - Dolan, James (1995)
Keywords: dept.phy; faculty_collection; sabbatical_report

[ Development of a Device That Would Continuously Monitor Build-up of Fluid in the Lungs ] - Wolf, Elizabeth (1990)
Keywords: dept.phy; faculty_collection; sabbatical_report

A video technique for the quantitative analysis of the Poisson spot and other diffraction patterns - Wein, G.R. (American Journal of Physics, 1999)
A new approach is presented for the observation and analysis of diffraction phenomena. Using the discussed procedures, direct comparison between measured light intensity and theoretical predictions is possible. A modified version of a Poisson spot experiment where the resulting diffraction pattern is recorded by a Sanyo vidicon camera is presented. A double slit experiment is also discussed, demonstrating the quantitative possibilities while addressing detector linearity. A video signal is connected directly to a computer and analyzed using public domain software. This is an excellent arrangement for demonstrations, student labs, or a more general diffraction experiment. © 1999 American Association of Physics Teachers.
10 citations (Crossref) [2023-10-31]
Keywords: dept.phy

A technique for measuring the 3-dimensional to 2-dimensional conductivity change of YBCO superconductors at the normal-to-superconducting phase change - Hmurcik, Lawrence V; Bidarian, A; Ibarra, B; Matthews, L D (Journal of Materials Science, 1998)
It is well known that conduction in YBa2Cu3O7 (YBCO) is by means of copper "planes" and "chains," where planes and chains describe the degree of bonding between copper and oxygen. Changes of conductivity versus temperature have been used to show that conduction in YBCO in the normal state is 3-dimensional, while conduction approaching the onset of the superconducting state is first 2-dimensional and then 3-dimensional. We have found another method to monitor this 2-to-3 transition. Using square samples, and measuring the voltage at each corner caused by a current applied to the opposite corners, one can find the conductivities along the x-axis and the y-axis. The ratio of these conductivities is unity for homogeneous samples in the normal state. However, in transition to the superconducting state, the ratio of conductivities changes. We examine this change as a function of sample purity, sample history, and exposure to an external magnetic field. Our data are consistent with data reported in the literature, and they suggest the existence of another state change deep in the superconducting state, which is only observable with the application of a magnetic field., Measurements were also carried out to correlate the anisotropy with sample porosity. Measurements of normal state resistivity, critical temperature, and critical current characterize the sample's porosity, and these data affect the anisotropy in the superconducting state in a manner directly proportional to the porosity., (C)1998 Kluwer Academic Publishers
1 citations (Crossref) [2023-10-31] Place: (C)1998 Kluwer Academic Publishers Publisher: (1)Science and Engineering, University of Bridgeport, Bridgeport, CT 06601, USA APS #MHM741373; E-mail: hmurcik@cse.bridgeport.edu
Keywords: Anisotropy; Critical temperature; Electric conductivity measurement; Electric current measurement; High temperature superconductors; Magnetic field effects; Oxide superconductors; Phase transitions; Porosity; Temperature measurement; Voltage measurement; Yttrium barium copper oxides; dept.phy